Regulation of Drosophila MKP-3 by Drosophila ERK. - Kim, S.E.; Kim, S.H.; Choi, K.Y. (Apoptosis: from signaling pathways to therapeutic tools., 2003)
DMKP-3 is a Drosophila dual-specificity phosphatase, which has high substrate specificity for Drosophila extracellular signal-regulated kinases (DERK). By in vitro reconstitution experiments, we found that DERK activates DMKP-3. Moreover, DMKP-3 was specifically activated by the addition of DERK but not by DJNK, Dp38, or Sevenmaker DERK D334N, a DMKP-3- binding mutant. The phosphatase activity of DMKP-3-R56A/R57A, a DERK-binding mutant, was not increased by DERK. Significantly, mammalian MKP-3 was also found to be activated by DERK. This cross-reactivity suggests a high level of conservation of the activation mechanism of ERK-specific phosphatases in Drosophila and mammals. When DMKP-3 was co-expressed with DERK in Drosophila Schneider cells, DMKP-3 protein levels increased, but this was not observed for the co-expressions of DJNK or Dp38. The stabilizations of the DERK binding mutants (DMKP-3-RR and DMKP-3-CA-RR) were not increased by DERK co-expression. Our results suggest that DERK specifically regulates DMKP-3 in terms of its enzyme activity and protein stability, and that direct protein-protein interaction is an essential aspect of this regulation.